A comparison of civilian (National Confidential Enquiry into Patient Outcome and Death) trauma standards with current practice in a deployed field hospital in Afghanistan. Issue 4 (20th July 2010) - Henning, D C W; Smith, J E; Patch, D; Lambert, A W
Abstract : Background: The National Confidential Enquiry into Patient Outcome and Death (NCEPOD) report on trauma management, published in 2007, defined standards for United Kingdom (UK) hospitals dealing with trauma. This study compared the NCEPOD standards with the performance of a UK military field hospital in Afghanistan. Setting: UK military field hospital, Camp Bastion, Helmand Province, Afghanistan. Materials and methods: Data were collected prospectively for all patients fulfilling the trauma team activation criteria during the 3 months of Operation Herrick IXa (from mid October 2008 to mid January 2009) and combined with a retrospective review of prehospital documentation, trauma resuscitation notes, operations notes and transfer notes for these patients. Results: During the study period, there were 226 trauma team activations. Of those patients brought to the medical facility at Camp Bastion by UK assets, 93.7% were accompanied by a doctor with advanced airway skills, although only 6.2% of the patients required such an intervention. Consultants in emergency medicine and anaesthesia were present in 100% of cases and were directly involved (in either leading the team or performing airway management) in 63.5% and 77.6% of cases respectively. Of those patients requiring operative intervention, 98.1% had this performed by a consultant surgeon. Of those patients requiring CT, 93.6% of cases had this performed within 1 h of arrival. Conclusions: Trauma patients presenting to the medical facility at Camp Bastion during Operation Herrick IXa, irrespective of their nationality or background, received a high standard of medical care when compared with the NCEPOD standards.